2023
DOI: 10.3390/ma16145154
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Polycaprolactone with Plant Extracts to Improve the Aging Resistance

Abstract: Natural extracts of plant origin are used as anti-aging compounds of biodegradable polymers. Coffee, cocoa, or cinnamon extracts in amounts from 0.5 to 10 wt.% were added to the polycaprolactone matrix. The manufactured materials were aged at elevated temperatures with increased relative humidity and continuous exposure to UV radiation for 720, 1440, or 2160 h. The performance of the proposed extracts was compared with the retail anti-aging compound, butylated hydroxytoluene. Visual assessment, FTIR analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The results suggest that polymers' performance against UV radiation can also benefit from enhanced communication structures, which elevate their anti-aging properties. Similar findings by Moraczewski et al [18] and Kockott [10] recommend the use of antiaging compounds to safeguard polymers from adverse UV radiations that cause aging, emphasizing the potential use of plant extracts to enhance aging resistance in polycaprolactone, thereby allowing polymers to be resistant to aging [18]. Some of these anti-aging components can be obtained abundantly from the natural extracts of coffee, cocoa, and cinnamon [18].…”
Section: Available Technical Methods For Improving the Performance Of...mentioning
confidence: 68%
See 3 more Smart Citations
“…The results suggest that polymers' performance against UV radiation can also benefit from enhanced communication structures, which elevate their anti-aging properties. Similar findings by Moraczewski et al [18] and Kockott [10] recommend the use of antiaging compounds to safeguard polymers from adverse UV radiations that cause aging, emphasizing the potential use of plant extracts to enhance aging resistance in polycaprolactone, thereby allowing polymers to be resistant to aging [18]. Some of these anti-aging components can be obtained abundantly from the natural extracts of coffee, cocoa, and cinnamon [18].…”
Section: Available Technical Methods For Improving the Performance Of...mentioning
confidence: 68%
“…However, anti-aging components can be used to shield polymers from degradation. For instance, Moraczewski et al [ 18 ] examined the possibility of modifying polycaprolactone using plant extracts to enhance its aging resistance. The findings suggest that natural extracts from coffee, cocoa, and cinnamon could be used to provide anti-aging components for biodegradable polymers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research [56] also demonstrated that compared with fibers without any plant extract, fibers including a plant extract had a decrease in Young's modulus and variation in the percentage of tensile deformation. This phenomenon also depends on the properties of the natural compounds incorporated into the fibers [57,58], and the increase or decrease in these parameters may be attributed to the different chemical interactions of the metabolites with the polymer [56]. The ANOVA analysis shows that there is no significant difference in the tensile deformation between the analyzed samples.…”
Section: Mechanical Characterizationmentioning
confidence: 97%